Development of a Patient-Centered Antipsychotic Medication Adherence Intervention. (June 2014) - Pyne, Jeffrey M.; Fischer, Ellen P.; Gilmore, LaNissa; McSweeney, Jean C.; Stewart, Katharine E.; Mittal, Dinesh; Bost, James E.; Valenstein, Marcia
Objective . A substantial gap exists between patients and their mental health providers about patient's perceived barriers, facilitators, and motivators (BFMs) for taking antipsychotic medications. This article describes how we used an intervention mapping (IM) framework coupled with qualitative and quantitative item-selection methods to develop an intervention to bridge this gap with the goal of improving antipsychotic medication adherence. Methods . IM is a stepwise method for developing and implementing health interventions. A previous study conducted in-depth qualitative interviews with patients diagnosed with schizophrenia and identified 477 BFMs associated with antipsychotic medication adherence. This article reports the results of using a variety of qualitative and quantitative item reduction and intervention development methods to transform the qualitative BFM data into a viable checklist and intervention. Results . The final BFM checklist included 76 items (28 barriers, 30 facilitators, and 18 motivators). An electronic and hard copy of the adherence progress note included a summary of current adherence, top three patient-identified barriers and top three facilitators and motivators, clarifying questions, and actionable adherence tips to address barriers during a typical clinical encounter. Discussion . The IM approach supplemented with qualitative and quantitative methods provided a useful framework for developing a practical and potentially sustainable antipsychotic medication adherence intervention. A similar approach to intervention development may be useful in other clinical situations where a substantial gap exists between patients and providers regarding medication adherence or other health behaviors.